SPIRITUALITY IN HIGHER EDUCATION: VIEWS OF THE TEACHING STAFF - Tālberga, Gunita; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Spirituality is an integral part of a holistic education (Miller, 2005) and a holistic development of personality (Chandler et al. 1992; Myers et al. 2008). Although various definitions of spirituality are used, several authors recognize the importance of spirituality in higher education (Dillard, 2006; Love & Talbot, 1999; Tisdel, 2001). Christian values have shaped the identity of Latvia since ancient times but the atheistic history of Latvia during the Soviet occupation has affected people's thinking. Therefore, the aim of this research was to find answers to the following questions – how do the teaching staff of the Latvian Academy of Sport Education (LASE) understand spirituality? What are the teaching staff's views on the enhancement of students' spirituality during their study process? What is the teaching staff's attitude regarding Biblical spirituality? This paper is based on a qualitative study (voluntary semi-structured interviews and qualitative content analysis were used) that examined 14 LASE teaching staff (7 women and 7 men, 27-68 years old). Spirituality is perceived as the multifaceted inner life of a person which determines a person's understanding of the universe and connection to God and other people. The common human and family responsibility, leadership and teaching staff responsibility, an institutional environment, and God's work in the hearts of students were mentioned as primary to enhancing spirituality in students. We observed that according to the Biblical understanding of spirituality most of the teaching staff appear to be in a stage of pre-spirituality and not spirituality.